Characteristics of transferrin saturation and anemia-related biomarkers in patients with uterine adenomyosis - Mari Kawamata; Fumitake Ito; Nanami Tahara; Akiyo Kakibuchi; Kazuya Yabumoto; Yuko Izumi; Akihisa Katayama; Taisuke Mori (PLoS ONE, 2026)
Background Ferritin may be elevated as an acute-phase reactant in inflammatory conditions, potentially masking iron deficiency. We aimed to evaluate the frequency of iron deficiency and the diagnostic significance of transferrin saturation (TSAT) in women with uterine adenomyosis. Methods This retrospective study included non-menopausal women aged 30–55 years who had iron metabolism markers measured at first visit. Anemia was defined as hemoglobin (Hb) <11 g/dL. Iron deficiency was defined using three criteria: ferritin-only (serum ferritin <20 ng/mL), TSAT-only (TSAT <20%), and a combined criterion (ferritin <20 ng/mL and/or TSAT <20%). Functional iron deficiency was defined as TSAT <20%, with ferritin ≥20 ng/mL. We compared the frequencies of anemia and iron deficiency across groups and evaluated correlations between Hb and TSAT (Pearson correlation using log-transformed TSAT; Spearman correlation as sensitivity analysis). Results Iron deficiency was more common than anemia in all patient groups. In the adenomyosis group, the frequency of iron deficiency based on the combined criterion (65.5%) was significantly higher than that diagnosed using ferritin alone (31.0%). In the myoma and no uterine structural abnormality groups, iron deficiency frequency was similar regardless of the diagnostic criteria. The correlation between Hb and log(TSAT) was weak in the adenomyosis group (r = 0.2123, p = 0.1771) but strong in the myoma (r = 0.5465, p < 0.0001) and no uterine structural abnormality groups (r = 0.6945, p < 0.0001). Spearman analyses showed the same qualitative pattern (adenomyosis ρ = 0.358, p = 0.020; myoma ρ = 0.576, p < 0.0001; no uterine structural abnormality ρ = 0.484, p = 0.0004). Agreement between ferritin- and TSAT-based classifications was fair (Cohen’s κ = 0.375; PABAK = 0.371), and a multivariable model for TSAT <20% with ferritin ≥20 ng/mL showed modest discrimination (AUC = 0.678). Conclusions Measuring TSAT and ferritin levels enhances the detection of iron deficiency in women with adenomyosis and may help identify functional iron deficiency when ferritin interpretability is limited by inflammation.